(untitled) (Ameghiniana, 2013)
In Hettangian and Sinemurian strata, especially cosmopolitan genera appear which are mostly comparable with species coming from other faunal provinces or at least are closely related to them. At uppermost Sinemurian (or/and lowermost Pliensbachian) time the faunal connexions with the Tethys must have been better than with Northwest Europe. In lower Pliensbachian strata another genus limited to Northwest Europe is found together with a cosmopolitan genus. Uptonia appears in South America in younger strata than in Northwest Europe. Together with this genus appears a new genus which is a forerunner of the Arnaltheidae. ""Radstockiceras’’ behrendseni is an endemic species for the Southamerican Pliensbachian. In middle and upper Pliensbachian strata, Radstockiceras (? = Fanninoceras) is more frequent than other genera, and there is evidence of better connexions with North America than with Europe. The family of Amaltheidae is totally missing, though a forerunner appears in South America. In lower Toarcian strata beside cosmopolitan species also genera and species are present which are limited to the Mediterranean faunal province or are at least more frequent there. With Bouleiceras appears a genus which had its main distribution in the Arabian-Madagascan province. One species each of Dactylioceratidae and Hildoceratidae were first described from the West Pacific region. In middle Toarcian strata three species of a genus of the Hildoceratidae, endemic for South America, appear and in upper Toarcian strata a further endemic genus is present. Likewise, Phlyseogrammoceras tenuicostatum is not closely related with species described from other regions. The forms found further in middle and upper Toarcian strata are well comparable with European genera and species. During Liassic time no faunistical differences can be identified within South America which then represents a uniforrn province of ammonites.